2020
DOI: 10.1002/acp.3735
|View full text |Cite
|
Sign up to set email alerts
|

The psychology of confessions: A comparison of expert and lay opinions

Abstract: Despite a body of confessions research that is generally accepted in the scientific community, courts often exclude experts on the ground that such testimony would not assist the jury, which can use its common sense. To examine whether laypeople know the contents of expert testimony on confessions, we asked 151 lay participants to indicate their beliefs about 30 confession-related statements used in a recent survey of 87 confession experts (Kassin et al., American Psychologist, 2018, 73, 63-80). Participants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Some studies have further demonstrated that mock jurors may be able to discount juvenile confessions stemming from a coercive interrogation (Najdowski & Bottoms, 2012). Nonetheless, prior research suggests that the public still fails to fully appreciate the risk that young age poses in interrogation contexts (Alceste et al, 2020; Mindthoff et al, 2018), which may explain why a portion of our sample still reported they would advise their child to waive their rights and speak to the police. Even more troublingly, the mere presence of an interested adult in the interrogation room has been found to lead potential jurors to be more likely to convict, regardless of whether the parent advised the child to waive or assert their Mirand a rights (Mindthoff et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Some studies have further demonstrated that mock jurors may be able to discount juvenile confessions stemming from a coercive interrogation (Najdowski & Bottoms, 2012). Nonetheless, prior research suggests that the public still fails to fully appreciate the risk that young age poses in interrogation contexts (Alceste et al, 2020; Mindthoff et al, 2018), which may explain why a portion of our sample still reported they would advise their child to waive their rights and speak to the police. Even more troublingly, the mere presence of an interested adult in the interrogation room has been found to lead potential jurors to be more likely to convict, regardless of whether the parent advised the child to waive or assert their Mirand a rights (Mindthoff et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Confessions are one of the most influential forms of testimonial evidence. Within the U.S. justice system confessions can be the sole basis for a conviction and are found compelling by jurors (Alceste et al, 2021). However, false confessions do occur and have been implicated in a significant proportion of wrongful convictions [DNA Exonerations in the United States ., 2023] (Innocence Project).…”
Section: Sleep-related Fatigue Can Increase False Confessionsmentioning
confidence: 99%
“…The available research suggests that potential jurors generally recognize accusatorial tactics as coercive and unacceptable (Henkel et al, 2008; Mindthoff et al, 2018; Moston & Fisher, 2007), but note that laypersons typically do not find accusatorial tactics as coercive as do social scientist experts (Alceste et al, 2021; Kaplan et al, 2020). Despite the demonstration of such beliefs, potential jurors report that accusatorial tactics are more likely to result in true (vs. false) confessions (Leo & Liu, 2009).…”
Section: Confessions Are Incriminating But Not Alwaysmentioning
confidence: 99%